Nível de atividade física e estado nutricional dos professores do Instituto Federal do Maranhão - PARPINELLI, Elynne Raphaella de Sousa Gonzaga (2023)
Introduction: Basic Education teachers are increasingly performing diverse functions and with less time to take care of their health, associating work activities to their lifestyle, and prone to develop non-communicable chronic diseases, which can be avoided from the balance between regular physical activity and healthy eating. It is important to evaluate the level of physical activity and the nutritional status of the teachers of the Federal Institute of Maranhão, since it can directly or indirectly impact the health and quality of life of this population. Objective: To evaluate the level of physical activity and the nutritional status of teachers at the Instituto Federal do Maranhão. Method: This was a quantitative, descriptive, field, survey and cross- sectional research, carried out with a sample of 70 teachers from 5 campuses of the Federal Institute of Maranhão, 59% male and 41% female, with mean age of 45.46 years, weight of 76.93 kilograms and height 1.67 meters. The data collection occurred through the use of an online questionnaire sent to the institutional e-mail of the teachers, containing the short version of the International Physical Activity Questionnaire and data to classify nutritional status, through the Body Mass Index. We carried out a descriptive analysis with presentation of quantitative data by means of mean and standard deviation. The Kruskal-Wallis test was used to verify the significant difference in BMI according to sex, age, and campus, and the chi-square test to verify the correlation between the level of physical activity and nutritional status. A 5% significance level was adopted for the analyses. The statistical program R Studio (R Core Team, 2021) was employed. Results: The levels of physical activity presented by the teachers comprised active (36%), irregularly active B (24%), irregularly active A (20%) and sedentary (6%). Regarding nutritional status 44% were overweight, 30% were of appropriate weight, 19% were grade I obese and 7% grade II obese. Conclusion: The highest percentage of teachers was active and the highest percentage found in the classification of nutritional status corresponded to overweight, showing that there was no correlation between physical activity level and nutritional status.